Women in change: female teachers and middle class in the 1940s-1950s - Şanlıtürk, Aslı Ebru. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2014., 2014)
This study examines the extent of liberation the middle class, educated, and working women enjoyed in Turkey during the 1940s-1950s, together with its restriction within the rules of the family, class and society. For this aim, interviews were conducted with eleven, female, middle class teachers who worked in secondary schools during the1940s and the 1950s. The concept of “liberation” is taken in a narrow sense in this study, referring only to the ability to direct their own lives and making life-changing choices such as about education, work life, and marriage without pressure. Secondary education teachers, working in junior high / high schools, were selected specifically, as they were required to receive university-level (faculty or institute) education in contrast to primary school teachers in the time period concerned.
Keywords: Women teachers -- Turkey -- History.; Women -- Turkey -- 20th century.